Evaluation Of Ultimate Resistance Of Steel-Concrete Composite Drilled Shafts Through Static Loading Tests - Moonkyung Chung (Deep Foundations Institute, 2010)
Static pile load tests were performed in order to evaluate bearing capacities and mechanical behaviors of three different pile types: (1) steel-concrete composite drilled shaft with rebar reinforcements inside the concrete, (2) steel-concrete composite drilled shaft without rebar, and (3) conventional drilled shaft (reinforcement concrete pile). The material elastic moduli obtained from pile load tests of steel-concrete composite drilled shafts with and without rebar reinforcement were found out to be similar. On the other hand, the elastic modulus of steel-concrete composite drilled shafts is almost twice as high as that of the conventional drilled shaft. The ultimate strengths of the steel-concrete composite drilled shaft with rebar, the steel-concrete composite drilled shaft without rebar, and the conventional drilled shaft were 9,810, 7,848, and 4,414kN, respectively. The results of these load tests reveal that the ultimate strengths of the steel-concrete composite drilled shaft with reinforcement and that without reinforcement are 2.22 times and 1.78 times greater that that of the drilled shaft. The structural failures of the steel-concrete composite drilled shafts occurred either at the boundary between tip of steel casing and rock-socketed concrete.